Emergency care, triage, and fairness - Lauridsen, Sigurd (Bioethics, 2020)
Triage is a widespread principle for prioritizing patients in emergency departments. The purpose of triage is to ensure that in emergency situations, whenever medical demand exceeds medical supply, limited resources should be directed to the case with the greatest clinical need. Triage fulfills this purpose by ranking patients according to how acute their condition is and then giving priority to the most acute ones. In this paper, I argue that this current practice of triage needs to be supplemented. Contemporary triage is based on a principle of preserving patients’ core capabilities, which is relevant when it comes to prioritizing acute patients above sub-acute ones, but not for prioritizing among sub-acute patients, which is the largest group of emergency patients. Henceforth, I propose to supplement triage with what I term the real dialogue model, a framework that, when combined with enhanced professional autonomy for clinical decision-makers, enables fair prioritizing among sub-acute patients.